Enhancing grid stability using dynamic reserve power point tracking techniques - Sajjan Kumar; G. R. Venkatakrishnan; R. Rengaraj; Amit Kumar; Pankaj Kumar (PLoS ONE, 2026)
Grid stability is of prime importance for grid-tied solar power systems as they are prone to power quality issues caused by the varying intensity of sun radiation and grid disturbances. To maintain grid stability, various PV power tracking algorithms have been developed. However, classical power tracking models often fail to maintain grid stability and sustain required power reserves under real-time variations in grid conditions and solar generation. To address this limitation, a Dynamic Reserve Power Point Tracking (DRPPT) control algorithm is proposed to ensure grid stability by dynamically adjusting reserve power. By continuously monitoring the PV array and grid conditions, the proposed controller determines the dynamic solar reserve power and accordingly selects the suitable operating mode. The operating point of PV array is then regulated by Flexible Power Point Tracking (FPPT) technique, which performs fine-tuning of the reference voltage followed by grid injection. By combining FPPT and Maximum Power Point Tracking (MPPT) functionalities, the proposed DRPPT controller maintains optimal reserve levels, ensuring the grid can rapidly respond to sudden changes in power supply or demand while meeting customer requirements. The proposed model is tested on hardware and simulated on software, and both results show the ability of DRPPT algorithm to handle real-time grid frequency changes and adapt the RPPT operation accordingly to meet grid stability standards. The proposed model has achieved superior THD mitigation, thereby improving grid stability, with 53.75%, 50%, and 7.5% lower THD compared to the conventional RPPT, Global FPPT (GFPPT), and Genetic Algorithm (GA)-based FPPT techniques, respectively.